Un maître de danse chez les Sauvages - Philippe Antoine (Viatica)
In his travel narratives (Travels in Greece, Palestine, Egypt, and Barbary, during the years 1806 and 1807, Voyages en Amérique) and his Memoirs, Chateaubriand notes the end of a “world of wilderness”. He focuses his attention on the art of dance in America, which for him had become the sign of a civilisation on the brink of extinction. Aware of the imminent obliteration of a world trekked by travellers, he thus seeks to record a History and a culture destined sooner or later to sink into oblivion.